Identity, Diaspora and Return in American Literature. - Oliver-Rotger, Maria Antònia (Routledge transnational perspectives on American literature., 2015)
This volume combines literary analysis and theoretical approaches to mobility, diasporic identities and the construction of space to explore the different ways in which the notion of return shapes contemporary ethnic writing such as fiction, ethnography, memoir, and film. Through a wide variety of ethnic experiences ranging from the Transatlantic, Asian American, Latino/a and Caribbean alongside their corresponding forms of displacement - political exile, war trauma, and economic migration - the essays in this collection connect the intimate experience of the returning subject to multiple loca.